Plasmodium vivax Malaria: A Case Review and Therapeutic Considerations in an Adult Patient - Cindy Elvionita; Aulia Azzahra; Muhammad Aldy Dermawan (LPPM Akafarma Sunan Giri Ponorogo, 2026)
Plasmodium vivax malaria remains a major health problem in tropical countries due to its high relapse rate and various hematological manifestations that may worsen the patient’s condition. This case report aimed to describe the clinical manifestations, laboratory findings, and evaluation of therapeutic rationality in a patient with Plasmodium vivax malaria during hospitalization. The study was conducted using a case report method involving a 22-year-old male patient who presented with periodic fever accompanied by chills for one week after traveling from a malaria-endemic area. Laboratory examination revealed microcytic hypochromic anemia, leukopenia, mild thrombocytopenia, and malaria parasites identified on peripheral blood smear examination. The patient received supportive therapy including intravenous Ringer Lactate fluid, paracetamol, omeprazole, domperidone, and ferrous sulfate, as well as definitive therapy consisting of dihydroartemisinin-piperaquine (DHP) for three days and primaquine for 14 days. The evaluation showed that most of the therapies administered were in accordance with national guidelines and WHO recommendations for uncomplicated P. vivax malaria. However, the absence of glucose-6-phosphate dehydrogenase (G6PD) enzyme activity testing prior to primaquine administration was considered one of the limitations in patient management. During hospitalization, the patient showed clinical improvement without severe complications. The management of P. vivax malaria requires a comprehensive approach including early diagnosis, rational therapy, clinical monitoring, and patient education to prevent relapse and improve therapeutic outcomes.